Rhetoric and identity: the episode of the centurion from Capernaum in the Evangelical Literature - Spléndido, Mariano (Romanitas - Revista de Estudos Grecolatinos, 2014)
The Gospels contain interesting episodes to analyse in order to observe the organizational conflicts of the first Christian communities in Orient. In the aftermath of the Jewish War, the Christian identities sought a definition amid tensions and debates with rabbinic Judaism. In this paper we propose to see some aspects of this process from the analysis of the account of the centurion of Capernaum and his sick slave. The evangelists confront Jesus with a gentile who performs an interesting defence of the concept of obedience by linking it with faith. The variants in writing will allow us to analyse the rhetorical interest of these communities, their organizational projects and their perspectives about the empire.